Explorando potencialidades da computação desplugada na rede estadual de educação de Mato Grosso - Sassi, Sabrina Bourscheid (2023)
The National Common Curricular Base (BNCC), as a guiding document for Brazilian schools, references to Computing, with emphasis on three axes: Digital World, Digital Culture and Computational Thinking (CP), in addition to related topics, such as Digital Information and Communication Technologies (DICT), digital resources and social networks. Although these axes are not presented in depth and even if there is an indication that they will be worked on in all curricular componentes in the BNCC, the PC axis is explicitly referenced in this document mainly in the Mathematics Area, when the text refers to mathematical processes, in the thematic units Algebra, Numbers, Geometry and Probability and Statistics, and the Digital Culture axis, is explicitly referenced in the Languages área. In turn, the Computing document complementing the BNCC in your organization for all stages of basic education, presents the three axes with their respective objects of knowledge, skills, explanations and examples, without specifically targeting a curricular componente. By analyzing the scenario of Brazilian public schools regarding access and availability of Digital Technologies, as well as student performance indicated in external and internal evaluations in general, we identified a context that can benefit from pedagogical practices involving the PC axes, Digital World and Digital Culture, through unplugged computing (UC). The UC comprises an approach that makes it possible to work on the three axes of the Computing área within the school curriculum, based on learning objectives, without using computer. In this regard, this work leads to a reflection around the following question: How the Digital World axes, Digital Culture and Computational Thinking can be addressed in Elementary School Final Years, through Unplugged Computing as an approach within the disciplines provided for in the Curricular Matrix of the State of Mato Grosso? In this sense, the objective of this research is to understand how students, teachers and school managers see the use of the Unplugged Computing approach for the study of concepts and skills from the axes Computational Thinking , Digital World and Digital Culture in the teaching-learning process in Elementary School. As a methodological strategy, we used participant research, adopting a qualitative approach. The research was developed with the participation of teachers, school managers and students from the 7th, 8th and 9th grade of an elementary state school in Sorriso – MT. This research contributes by proposing an interdisciplinary planning for Elementary School that can be replicated and adapted for other school stages and for other research; describing the development of unplugged activities and the relationship established with the disciplines of the BNCC, considering the context in which they were inserted; sharing findings that can be used by researchers in the field of Education and Computing who are working with Unplugged Computing, Computing in Basic Education, BNCC and its complement, axes Computational Thinking, Digital World and Digital Culture.